Does renal transplant in children with LUTD improve their bladder function?. (30th May 2020) - Aboulela, Waseem; Fawzy, Ahmed M.; Abdelmawla, Mohamed A.; Salah, Doaa M.; Eldin, Mohamed Salah; Mohamed Anwar, Ahmed Zaki; El Ghoneimy, Mohamed; Shouman, Ahmed M.; Shoukry, Ahmed I.; Bazaraa, Hafez; Tawfiek, Ehab R.; Fadel, Fatina; et al.
Abstract: Much is still unknown about LUT function after receiving renal graft. Graft function was the main focus of different studies discussing the same issue. However, these studies ignored the effects of the graft on lower tract function and more demand for bladder cycling and growth of the child. Therefore, we aimed at evaluating the LUT function after RT into patients with LUTD. We enrolled a retrospective cohort of 83 live renal transplant children with LUTD. The 44 patients in Group (A) had a defunctionalized bladder, and the 39 patients in Group (B) had underlying LUT pathology. All patients had clinical and urodynamic evaluation of LUT functions at least 1 year after RT. We found that the improvement in patients with impaired bladder compliance was 73% in Group (A) and 60% in Group (B), with no statistically significant difference between the study groups. In Group (B), there was statistically significant worsening of MFP (8.4%) and mean PVR (79.9%) after RT. In Group (A), mild but stable significant improvement of all clinical and urodynamic parameters was observed. Serum creatinine was significantly worse in patients with pathological LUTD compared with those with defunctionalized bladder but without significant effect on graft survival. All LUT variables seemed to have no adverse effect on graft survival except for use of CIC and augmented bladder. Incident UTI independent of LUT variables accounted for 20% of graft creatinine change.